2022
DOI: 10.1177/20503121221117853
|View full text |Cite
|
Sign up to set email alerts
|

Malaria infection and its association with socio-demographics, preventive measures, and co-morbid ailments among adult febrile patients in rural Southwestern Nigeria: A cross-sectional study

Abstract: Objectives: The study determined the prevalence of malaria infection and its association with socio-demographics, environmental, housing, and co-morbid ailment factors. Methods: The study was a cross-sectional of 330 consented adult febrile patients who were recruited at a tertiary health facility in rural Southwestern Nigeria. The standardized interviewer-administered questionnaire sought information on their socio-demographics, environmental, housing, and co-morbid ailment factors. Venous blood samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 34 publications
3
15
2
Order By: Relevance
“…It is possible that, unlike immunity to other infectious diseases, malaria immunity – the mechanisms of which are not yet fully elucidated – is not significantly impacted by comorbidity among people living in malarial endemic zones such as Nigeria. This finding is however contrary to the reports by Chukwuocha et al 15 and Ibrahim et al 30 who, respectively, demonstrated statistical association between malaria infection and certain NCDs. Also, studies in non-endemic regions among patients, who returned from endemic areas, showed significant association between NCDs and the risk of malaria infection as well as its severity.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…It is possible that, unlike immunity to other infectious diseases, malaria immunity – the mechanisms of which are not yet fully elucidated – is not significantly impacted by comorbidity among people living in malarial endemic zones such as Nigeria. This finding is however contrary to the reports by Chukwuocha et al 15 and Ibrahim et al 30 who, respectively, demonstrated statistical association between malaria infection and certain NCDs. Also, studies in non-endemic regions among patients, who returned from endemic areas, showed significant association between NCDs and the risk of malaria infection as well as its severity.…”
Section: Discussioncontrasting
confidence: 94%
“…The studies by Chukwuocha et al. 15 and Ibrahim et al, 30 for example, were facility-based studies among symptomatic patients who presented for care and are more likely to have more severe forms of malaria than the respondents in our study, which was community based.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations